Agricultural Communicators in Education - Jim Shaner; Don Esslinger (Journal of Applied Communications, 1980)
Editorial back matter for vol.63, no.3, July-Sept. (1980) of The ACE Quarterly, Official Journal of the Agricultural Communicators in Education